Credit risk securitization and bank soundness: Evidence from the microlevel for Europe - Michalak, Tobias C.; Uhde, André (Quarterly Review of Economics and Finance)
Using a unique sample of 749 cash and synthetic securitization transactions issued by 60 stock-listed bank holdings in the EU-13 plus Switzerland over the period from 1997 to 2007 this paper provides empirical evidence that credit risk securitization has a negative impact on the issuing banks’ financial soundness. Baseline findings hold even when controlling for likely reverse causality by employing instrumental variable techniques and substituting the accounting-based z-score ratio by market-based indicators of bank risk. Moreover, investigating the relationship between credit risk securitization and single z-score components in order to evaluate significant transmission channels proposed by relevant theoretical literature, we find a negative impact of securitization on bank profitability and capital environment as well as a positive relationship between securitization and the issuing bank's return volatility. Against the background of our empirical results we underline that the decision by the Basel Committee to enhance the new Basel III framework in the field of securitization is a step in the right direction.
Keywords: Credit risk securitization Bank soundness European banking

Cross-border bank lending - Empirical evidence on further determinants from OECD banking markets - Müller, Oliver; Uhde, André (Journal of International Financial Markets, Institutions & Money)
Employing data on foreign bank claims from 13 OECD countries on 51 emerging markets between 1993 and 2007, this study investigates specific characteristics of OECD banking markets and lending banks as new important determinants of cross-border lending. We initially provide empirical evidence that in addition to well-accepted “gravity measures”, characteristics of OECD banking markets as well as lending banks’ attributes may describe further important determinants of cross-border bank lending with regard to our sample. Building subsamples of more-developed emerging markets vs. frontier markets, addressing (non) common lender relationships and analyzing cross border lending flows during different time periods, our analysis additionally reveals that both the determinants’ explanatory power and their direction of impact notably vary with respective subsamples.
Keywords: Foreign bank claims; Gravity measures; OECD banking markets’ characteristics; Lending banks’ characteristics

Wealth effects of credit risk securitization in European Banking - Farruggio, Christian; Michalak, Tobias C.; Uhde, André (Journal of Business Finance and Accounting)
Using a unique cross‐sectional dataset of 381 cash and synthetic securitizations issued by 53 banks from the EU‐15 plus Switzerland between 1997 and 2007, this paper provides empirical evidence for time‐dependent negative wealth effects of credit risk securitization announcements in European banking. Baseline results hold when comparing estimated wealth effects with a control group of similar but non‐securitizing banks for the relevant time period. Moreover, building several sub samples we find that the nexus between credit risk securitization, the issuing banks’ overall risk exposure and wealth effects is associated with a variety of transaction‐ and bank‐specific factors.
Keywords: wealth effects; credit risk securitization; Europe; event study

Measuring the quality of banking supervision revisited - Assessments by German banks before and during the financial crisis - Paul, Stephan; Stein, Stefan; Uhde, André (Journal of Governance and Regulation)
This contribution presents and discusses main results of a new survey on the assessment of supervisory quality among German banks in 2010. In particular, it is analyzed if and how supervised banks’ perception of the quality of supervisory authorities and their instruments has changed due to the financial crisis starting in mid-2007. Subsequently, results from the recent survey are compared with findings provided by a former study carried out by the authors in 2006 (Paul, Stein and Uhde, 2008).
Keywords: banking supervision; quality; assessment; banking sector

Sovereign Risk and Bank-Specific CDS Pricing - Meine, Christian; Michalak, Tobias C.; Uhde, André
Employing time series of single-name CDS market spreads from 29 European banks located in the EU-12 plus Switzerland and the UK over the period from January 2004 through September 2010 this paper analyses the relationship between increasing sovereign risk and bank-specific CDS pricing. Results from calculating relative CDS spread deviations (model minus market spreads) initially reveal a price bubble in the European CDS market until the beginning of the financial crisis in mid-2007. From this point in time the gap narrows remarkably during the financial crisis and sovereign debt crisis period. Corresponding to these findings, the empirical analysis reveals a negative impact of sovereign risk on calculated CDS spread differentials indicating a spill-over effect between sovereign risk and bank risk and hence, a positive effect on bank-specific CDS pricing. Further analyses reveal that the perception of sovereign risk is not crisis- but country-dependent suggesting that bank-specific CDS market spreads may already include a premium to cover sovereign risk from PIIGS countries during the pre-crisis period in Europe.
Keywords: Sovereign risk; Structural credit risk models; bank-specific CDS pricing

Zur Neuregulierung des Bankensektors nach der Finanzkrise: Bewertung der Reformvorhaben der EU aus ordnungspolitischer Sicht - Haucap, Justus; Heimeshoff, Ulrich; Uhde, André (Die aktuelle Finanzkrise: Bestandsaufnahme und Lehren für die Zukunft, Schriften zur Ordnungsfragen der Wirtschaft)
Im Zuge der in den USA durch die exzessive Vergabe von Subprime-Krediten und deren Verbriefung ausgelöste Finanzkrise und der daraus folgenden weltweiten Wirtschaftskrise hat sich gezeigt, dass das bisherige System der Regulierung bzw. Überwachung von Finanzinstitutionen nicht ausreichend ist. Sowohl in den USA als auch in der Europäischen Union wird deshalb intensiv über ein neues System zur Regulierung von Finanzinstituten nachgedacht. Es ist zwar offen-sichtlich, dass eine wesentliche Ursache der Finanzkrise in den USA die Ermunterung der Finanzinstitute durch den Staat zur Vergabe von Immobilienkrediten an nicht ausreichend solvente Konsumenten war. Die vorhandenen Regulierungsinstrumente konnten die Krise jedoch nicht verhindern bzw. ausreichen abmildern. Das vorliegende Papier setzt sich zum Ziel, die Vorschläge zur Reform der Bankenregulierung zu evaluieren und insbesondere auf ihre potenziellen Wirkungen im Hinblick auf den Wettbewerb im Bankensektor zu überprüfen. Im Zuge der Diskussion über mögliche Lösungen existieren verschiedenste Vorschläge, die von Änderungen in Rechnungslegungsvorschriften über die Neuordnung der nationalen bzw. internationalen Finanzaufsicht bis hin zu einer stärkeren Berücksichtigung systemischer Risiken gehen. Die Auswirkungen der Finanzkrise haben gezeigt, dass die Abkehr von herkömmlichen Rechnungslegungssystemen hin zu Regeln der internationalen Rechnungslegung unter dem Schlagwort „Fair Value Accounting“ durchaus Gefahren in sich bergen kann. Die Debatte dreht sich insbesondere um die Frage, ob die neuen Rechnungslegungsvorschriften maßgeblich dazu beitragen, das regulatorische Eigenkapital einer Bank in Boomphasen zu erhöhen und in konjunkturellen Schwächephasen dagegen zu senken. In der Literatur ist in Hinblick auf diese Frage bislang keine einhellige Auffassung zu identifizieren. Pellens et al. (2009) gelangen zu dem Ergebnis, dass bankenaufsichtsrechtliche Normen an das IFRS-Zahlenwerk gebunden sind und dies für regulatorische Entscheidungen als besonders kritisch zu sehen ist. Durch das Konzept des Fair-Value-Accounting wurde das regulatorische Eigenkapital im Zeitraum von 2003 bis 2007 systematisch erhöht, woraus ein gestiegener Kreditvergabespielraum resultierte. Demgegenüber kommen Laux und Leuz (2009) im Rahmen einer empirischen Studie anhand von Mikrodaten aus den USA zu dem Ergebnis, dass Fair-Value-Accounting nur zum geringen Teil zu den Problemen der US Banken beigetragen hat und es im Rahmen ihrer Studie keine Evidenz für wesentliche Effekte dieses Rechnungslegungsverfahrens auf die massiven Abschreibungen der US Banken gibt. Beide Studien betonen aber auch, dass weitere empirische Forschung notwendig ist, bevor diese Frage abschließend geklärt werden kann. Die Frage des adäquaten Rechnungslegungssystems zeigt, wie vielfältig die Ursachen der gegenwärtigen Finanzkrise sind und wie schwer tatsächliche kausale Effekte zu identifizieren sind. Im folgenden Abschnitt werden zunächst die ordnungspolitischen Rahmenbedingungen einer angemessenen Bankenregulierung dargestellt. Der dritte Abschnitt umfasst einen kurzen Überblick über den Verlauf der Finanzkrise. In Abschnitt 4 diskutieren wir die wesentlichen Vorschläge zur Optimierung der Regulierung von Finanzinstituten. Abschnitt 5 evaluiert diese Vorschläge auch aus einer wettbewerbsökonomischen Perspektive. Diese Perspektive ist aus unserer Sicht vor allen Dingen notwendig, weil eine großer Teil der Reformdebatte aus Sicht der Finanzmarktstabilität geführt wird und infolgedessen Wettbewerbseffekte vernachlässigt werden. Das Fazit in Abschnitt 6 fasst unsere Ergebnisse zusammen und gibt einen Ausblick auf weiteren Forschungsbedarf aus Sicht der Wettbewerbsökonomie.

Ökonomische Möglichkeiten und Auswirkungen von Wettbewerb bei Zentralverwahrern für Bundeswertpapiere. Gutachten im Auftrag des Bundesministeriums für Finanzen (BMF). Gutachten fg 1/10 - Uhde, André; Haucap, Justus; Heimeshoff, Ulrich

The nexus between monetary policy, banking market structures and bank risk-taking - Uhde, André; Michalak, Tobias
Using a sample of stock-listed bank holding companies located in Western Europe over the period from 1997 to 2008 this paper provides empirical evidence that an increase in short-term interest rates as well as an extended period of expansionary monetary policy has a negative impact on European stock-listed banks’ soundness as measured by the Expected Default Frequency. Against this background and in order to evaluate interactions between the risk-taking channel of monetary policy and the competitiveness of a country’s banking market we find a negative impact of an increase in competition in the loan market – proxied by the Boone-indicator – on financial soundness. Referring to the structural-conduct performance (SCP) paradigm, this paper provides further evidence that an increase in concentration in the banking market spurs financial soundness.

The Nexus between Monetary Policy, Banking Market Structure and Bank Risk Taking - Michalak, Tobias C.; Uhde, André
Using a sample of stock-listed bank holding companies located in Western Europe over the period from 1997 to 2008 this paper provides empirical evidence that an increase in short-term interest rates as well as an extended period of expansionary monetary policy has a negative impact on European stock-listed banks’ soundness as measured by the Expected Default Frequency. Against this background and in order to evaluate interactions between the risk-taking channel of monetary policy and the competitiveness of a country’s banking market we find a negative impact of an increase in competition in the loan market – proxied by the Boone-indicator – on financial soundness. Referring to the structural-conduct performance (SCP) paradigm, this paper provides further evidence that an increase in concentration in the banking market spurs financial soundness.
Keywords: risk-taking channel; competition; concentration; bank soundness; European banking

Einheitlicher europäischer Bankenmarkt? Eine Einschätzung der Wettbewerbssituation vor und nach der Finanzkrise - Paul, Stephan; Uhde, André (Wirtschaftsdienst)
Die schwerste Finanz- und Wirtschaftskrise nach dem Zweiten Weltkrieg befindet sich nun schon in ihrem dritten Jahr und wird in weiten Teilen der Öffentlichkeit als Paradebeispiel für ein gravierendes Marktversagen eingestuft. Dies hat über die unmittelbaren staatlichen Rettungsmaßnahmen hinaus den Ruf nach "Mehr Staat in der Kreditwirtschaft!" verstärkt und vielfältige Vorschläge zur Ausweitung und Verschärfung der Beaufsichtigung der Banken hervorgerufen (zuletzt im September 2009 beim Finanzgipfel in Pittsburgh). Noch lässt sich nicht präzise genug abschätzen, welche staatlichen Hilfen für die Kreditwirtschaft erforderlich sein werden und welche Veränderungen in der Bankenregulierung noch vorgenommen werden müssen. Dennoch wird in diesem Beitrag der Versuch einer Skizze möglicher Auswirkungen auf die Wettbewerbssituation des europäischen und deutschen Bankenmarktes speziell im Retail-Segment unternommen. Um die durch die Finanzkrise hervorgerufenen Veränderungen einschätzen zu können, ist jedoch zunächst ein kurzer Blick auf die wichtigsten Etappen und Ergebnisse der europäischen Finanzmarktintegration erforderlich.
Keywords: Finanz- und Wirtschaftskrise; Bankenmarkt